Analyzing Translation Methods by English Department Students in North Sumatra: Poetry Translation Case Study - Tanzila Bahar; Larasati Dwi Wahyuni; Farida Repelitawaty Kembaren (Universitas Maritim AMNI Semarang, 2024)
Poetry translation is a complex and challenging process, as poetry is a rich and unique form of language that often uses poetic words and sentence structures. This study aims to analyze the translation methods used by students of English Language Education Study Program in translating poetry from Indonesian to English. This research uses a case study method involving 15 students of English Education in North Sumatera who are currently undergoing a translation course. The research data were obtained through analyzing the poetry translations produced by the students. The results showed that the students used various translation methods, but the most commonly used method was literal translation. Students also managed to maintain the meaning of the original poem in their translations, but they sometimes struggled to convey the emotional and aesthetic nuances of the poem. Based on the results of the study, the researcher concludes that PBI students still need to develop their skills in translating poetry. This can be done by providing more in-depth learning about the theory and practice of poetry translation, as well as providing opportunities for students to practice translating poetry with guidance from experienced lecturers.